Overspeed correction scheme for dc motor using artifical intelligent approach - Bollah, Javadius (2013)
The conventional PI, PD and PID controllers were used as a control strategy for various industrial processes from many years due to their simplicity in operation. They used mathematical models to control the plant for different process control applications. A fuzzy controller for DC speed motor fed by DC Chopper, H-Bridge converter is developed and presented in this paper. Fuzzy logic based control systems were introduced by Lotfi Zadeh to optimize the speed and process control parameters in better way. During implement this project, we have an experienced in modeling the physical quantities such as dc motor, and modeling a mathematical equations for dc motor, develop simulink block for PI controller and then develop fuzzy logic speed controller using MATLAB Simulink blocks.